Case Report: MSS colorectal extrahepatic (non-liver) metastases as the dominant population for immunotherapy combined with multi-target tyrosine kinase inhibitors - Liu, Jiayin; Li, Dan; Han, Jing; Zhang, Yin; Zhang, Xue; Fan, Zhisong; Feng, Li; Wang, Long; Jin, Hui; Zuo, Jing; Wang, Yudong (Frontiers in Oncology, 2023)
Background The microsatellite stability(MSS) subtype of Colorectal Cancer(CRC) represents approximately 95% of mCRC cases. Immunotherapy was not as encouraging as the data for MSS mCRC cancer. We report the treatment of a series of patients with extrahepatic metastasis of MSS colorectal cancer, which can provide reference and guidance for the treatment of non-hepatic metastasis of MSS colorectal. Case presentation This report describes 8 typical cases of successful MSS treatment with lung metastases of CRC. We systematically reviewed the clinical data and detailed medical history of one of these patients with extrahepatic metastasis from MSS colorectal cancer, and reviewed the literature to analyze and discuss the related epidemiological features, mechanisms and recent research findings of the special subgroup of the population. Conclusions Although MSS colon rectal cancer is still known as a cold tumor in the industry, immunotherapy combined with multi-targeted anti-vascular tyrosine kinase inhibitors had brought clinical benefits to patients with non-hepatic metastases from MSS colorectal cancer.